2006
DOI: 10.7202/014081ar
|View full text |Cite
|
Sign up to set email alerts
|

Les territoires de l’homosexualité à Bruxelles : visibles et invisibles

Abstract: À l’image de nombreuses villes occidentales, Bruxelles a récemment vu émerger un quartier gai dans une portion de son espace central, à savoir le quartier Saint-Jacques. Fondé sur des recherches empiriques, cet article veut mettre en lumière la nature de ce nouveau type d’espace d’homosociabilité et à l’inscrire dans une géographie des multiples territoires homosexuels, plus ou moins marqués dans le paysage urbain, à l’échelle de l’ensemble de la ville. La concentration des manifestations les plus visibles de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…16 While the spatial distribution of homosexual meeting places extends beyond the central and visible gay neighbourhood [Deligne et al, 2006], Rue du Marché au Charbon is nevertheless widely identified in social and media rhetoric as an important area in Brussels homosexual life. And for good reason: bars, nightclubs, saunas, sex clubs as well as more "traditional" businesses, such as hairdressers or clothing shops, exist in an identified commercial setting (signs, advertisements, rainbow flags, etc.)…”
Section: A Sexuality Bordermentioning
confidence: 99%
“…16 While the spatial distribution of homosexual meeting places extends beyond the central and visible gay neighbourhood [Deligne et al, 2006], Rue du Marché au Charbon is nevertheless widely identified in social and media rhetoric as an important area in Brussels homosexual life. And for good reason: bars, nightclubs, saunas, sex clubs as well as more "traditional" businesses, such as hairdressers or clothing shops, exist in an identified commercial setting (signs, advertisements, rainbow flags, etc.)…”
Section: A Sexuality Bordermentioning
confidence: 99%
“…Hoewel de ruimtelijke spreiding van de ontmoetingsplaatsen voor homoseksuelen verder gaat dan de zichtbare en centrale homowijk [Deligne et al, 2006 [Goffman, 1973], waartegen de voorstelling van de activiteiten van de homowijk logisch en tastbaar wordt en de grenzen ervan vastlegt. Uit de interviews komt overigens naar voren dat deze voorstelling gepaard gaat met een geaardheidsgerelateerde projectie van de activiteiten in de straat, die wordt gevoed door de handelszaken, symbolen en praktijken (zoals het zichtbare homoseksuele geflirt).…”
Section: Een Geaardheidsgrens?unclassified
“…C'est notamment le cas pour les membres de l'importante communauté homosexuelle locale, qui y trouvent des ressources en termes de sociabilité, de commerces et de loisirs mais aussi un confort de vie plus grand que dans des quartiers socialement homogènes. Au-delà du cas de Brixton, la participation des populations homosexuelles à des processus de gentrification commerciale ou résidentielle constitue un sujet à approfondir (Deligne et al, 2006).…”
Section: Londres « Ville Expérimentale » De La Nouvelle Gentrificatiunclassified